Plan de marketing estratégico para la empresa florícola “ROSE SUCCESS” provincia de Cotopaxi parroquia Tanicuchi periodo 2013 - Jami Toaquiza, Luisa Maritza (2015)
The Strategic Marketing Plan presents price, product, place, promotion and strategies for each department, these strategies will be good for ROSE SUCCESS can reach its objectives, exploiting internal strengths and external opportunities in the market. The level of customer satisfaction in SUCCESS ROSE is at a moderate level for which it is important to apply marketing strategies that arises to maintain or improve the level of customer satisfaction as it will be one of the key factors to the Company to continue growing and reaching success in foreign markets while maintaining an organizational culture focused on customer satisfaction. At the end of the project we present the operational plan which is the implementation of strategies to achieve the goals that the company has adequate staff to designate compliance, for which it is necessary for all company employees know the plan.